Intrinsic disorder and coiled coil formation in prostate apoptosis response factor-4 (Par-4) : submitted in fulfilment of the requirements of the degree of Doctor of Philosphy, Institute of Fundamental Sciences, Massey University, New Zealand - Schwalbe, Martin (Massey University, 2010)
Prostate apoptosis response factor-4 (Par-4) is a ubiquitously expressed pro-apoptotic and tumour suppressive protein. Par-4 contains a highly conserved coiled coil (CC) region at the Cterminus, particularly the distal 40 residues fulfil the criteria for a leucine zipper (LZ). This Cterminal domain serves as the primary recognition domain for a large number of binding partners. Par-4 is tightly regulated by the aforementioned binding partners and also by posttranslational modifications. Biophysical data presented here describe Par-4 as primarily an intrinsically disordered protein (IDP). Bioinformatic analysis of the highly conserved Par-4 reveals low sequence complexity and enrichment in polar and charged amino acids. High proteolytic susceptibility and increased hydrodynamic radii are consistent with largely extended structures in solution. Spectroscopic measurements using circular dichroism (CD) and nuclear magnetic resonance (NMR) also reveal characteristic features of intrinsic disorder. Under physiological conditions, data show that Par-4 self-associates via the C-terminal domain possibly through coiled coil formation. Analysis of various constructs comprising the Par-4 LZ domain by NMR, CD, light scattering and other techniques reveals an environment-dependent conformational equilibrium between primarily disordered monomers and predominantly coiled coil dimers. Whereas the disordered monomers are easily observed by NMR, the coiled coil fraction is not amenable to NMR studies possibly due to intermediate exchange processes. Mutational approaches that stabilise the coiled coil fraction result in NMR spectra of lower quality compared to the wild-type form. The high degree of sequence conservation suggest that coiled coil formation and intrinsic disorder are essential for Par-4 to function as an effective regulator of apoptosis.
Keywords: Binding proteins; Protein NMR; Fields of Research::270000 Biological Sciences::270100 Biochemistry and Cell Biology